Minimum alcohol pricing policies in practice: A critical examination of implementation in Canada - Thompson, K.; Stockwell, Tim; Wettlaufer, A.; Giesbrecht, N.; Thomas, G. (2017)
There is an interest globally in using Minimum Unit Pricing (MUP) of alcohol to promote public health. Canada is the only country to have both implemented and evaluated some forms of minimum alcohol prices, albeit in ways that fall short of MUP. To inform these international debates, we describe the degree to which minimum alcohol prices in Canada meet recommended criteria for being an effective public health policy. We collected data on the implementation of minimum pricing with respect to (1) breadth of application, (2) indexation to inflation and (3) adjustments for alcohol content. Some jurisdictions have implemented recommended practices with respect to minimum prices; however, the full harm reduction potential of minimum pricing is not fully realised due to incomplete implementation. Key concerns include the following: (1) the exclusion of minimum prices for several beverage categories, (2) minimum prices below the recommended minima and (3) prices are not regularly adjusted for inflation or alcohol content. We provide recommendations for best practices when implementing minimum pricing policy.